2018
DOI: 10.2196/preprints.9957
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Computerized Method for Measuring Computed Tomography Pulmonary Angiography Yield in the Emergency Department: Validation Study (Preprint)

Abstract: Background: Use of computed tomography pulmonary angiography (CTPA) in the assessment for pulmonary embolism (PE) has significantly increased over the past two decades. While this technology has improved the accuracy of radiologic testing for PE, CTPA also carries the risk of significant iatrogenic harm. Each CTPA carries a 14% risk of contrast induced nephropathy and a lifetime malignancy risk that can be as high as 2.76%. Appropriate use of CTPA can be estimated by monitoring CTPA yield, the percentage of te… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…As was previously validated, CTPA yield was calculated as the number of ED CTPA orders linked to an inpatient discharge diagnosis of PE divided by the total number CTPAs completed (18). Our validation study found 96.4% accuracy using this method which utilizes EHR reports and not billing data.…”
Section: Computerized Ctpa Yield Calculationmentioning
confidence: 70%
See 1 more Smart Citation
“…As was previously validated, CTPA yield was calculated as the number of ED CTPA orders linked to an inpatient discharge diagnosis of PE divided by the total number CTPAs completed (18). Our validation study found 96.4% accuracy using this method which utilizes EHR reports and not billing data.…”
Section: Computerized Ctpa Yield Calculationmentioning
confidence: 70%
“…In the rare, but potentially growing, number of cases in which a patient is diagnosed with PE, but discharged directly from the ED, our methodology would lead us to interpret this situation as a negative CTPA, falsely decreasing CTPA yield. This was a rare occurrence however in our validation study (44). Additionally, in the rare case that a provider orders a CTPA as well as a CTA abdomen/pelvis to evaluate for both PE and aortic disease the study would be eliminated.…”
Section: Limitationsmentioning
confidence: 97%